Severe CSF immune cell alterations in cryptococcal meningitis gradually resolve during antifungal therapy - Christine Dambietz; Michael Heming; Tobias J. Brix; Andreas Schulte-Mecklenbeck; Phil-Robin Tepasse; Catharina C. Gross; Jonel Trebicka; Heinz Wiendl; Gerd Meyer zu Hörste (BMC Neurology)
Abstract Cryptococcal meningitis (CM) is a severe fungal disease in immunocompromised patients affecting the central nervous system (CNS). Host response and immunological alterations in the cerebrospinal fluid (CSF) after invasion of Cryptococcus neoformans to the central nervous system have been investigated before but rigorous and comprehensive studies examining cellular changes in the CSF of patients with cryptococccal meningitis are still rare. We retrospectively collected CSF analysis and flow cytometry data of CSF and blood in patients with CM (n = 7) and compared them to HIV positive patients without meningitis (n = 13) and HIV negative healthy controls (n = 7). Within the group of patients with CM we compared those with HIV infection (n = 3) or other immunocompromised conditions (n = 4). Flow cytometry analysis revealed an elevation of natural killer cells and natural killer T cells in the CSF and blood of HIV negative patients with CM, pointing to innate immune activation in early stages after fungal invasion. HIV positive patients with CM exhibited stronger blood-CSF-barrier disruption. Follow-up CSF analysis over up to 150 days showed heterogeneous cellular courses in CM patients with slow normalization of CSF after induction of antifungal therapy.